Empowering the Santri’s Reading Skills in Pesantren Mahasiswa Al-Hikam Malang - Ja'far, Handoko (Abdi: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
This study addresses the prevalent challenges in reading faced by santri within Islamic boarding schools and proposes a solution through an extensive reading program. Many santri encounter difficulties in comprehending texts, particularly when dealing with English materials. The primary obstacle identified is a lack of vocabulary, ranging from limited knowledge to a deficiency in mastery. Additionally, deficiencies in reading skills, such as skimming, making inferences, and identifying key ideas, contribute to the overall reading struggle. To address these issues, a method, namely Sustained Silent Reading (SSR), was implemented, assuming that santri would enhance their reading ability and develop an interest in reading through extensive reading. An accompaniment program was conducted to emphasize the importance of reading, aiming to increase motivation and cultivate a reading culture among santri. The theoretical contribution of this program is expected to support existing theories related to the automatic recognition of words, vocabulary knowledge, and learner autonomy. On a practical level, the results can serve as a reference for designing similar programs targeting other language skills, providing an alternative and effective method for language accompaniment. Moreover, the pesantren foundation can use the outcomes as a reference to support the establishment of a reading culture, potentially enhancing the pesantren library.